0351 National prevalence of occupational noise exposure. (21st August 2017) - Fritschi, Lin; Lewkowski, Katherine; Heyworth, Jane; Li, Ian; McCausland, Kahlia; Williams, Warwick
Abstract : Noise-induced hearing loss (NIHL) is common and is one of the major costs to occupational compensation schemes. NIHL can also result in reduced quality of life and employment opportunities for the worker. Despite this considerable burden, there is little understanding of occupational noise exposure on a national scale. Recognition of occupational noise exposure is particularly important for small businesses which employ the majority of workers, and are less likely to monitor occupational health concerns. We undertook a national phone survey of nearly 5000 workers in Australia using our validated online application, OccIDEAS. In order to mirror a dosimeter survey, each person was asked about their last working day. Each worker was allocated one of 52 job-specific modules which contained questions about relevant tools, tasks and the time spent on each tool/task. The answers were linked to a custom database containing typical noise levels for each tool/task. Partial noise exposures were calculated, added and normalised to an eight hour shift. On their previous working day, 16% of respondents (23% of males and 7% of females) had an estimated exposure (LAeq, 8h) equal to or over the recommended exposure limit of 85 dB. Of those exposed above the limit, 80% were males. A substantial proportion of those exposed above the exposure limit reported that they did not wear hearing protection at all during the day. These results can be used to target interventions at particular occupational and demographic groups to reduce the incidence of NIHL in the future.